Protein phosphatase PHLPP1 controls the light-induced resetting of the circadian clock - Satoru Masubuchi; Tianyan Gao; Audrey O’Neill; Kristin Eckel‐Mahan; Alexandra C. Newton; Paolo Sassone–Corsi (2010)
The pleckstrin homology domain leucine-rich repeat protein phosphatase 1 (PHLPP1) differentially attenuates Akt, PKC, and ERK1/2 signaling, thereby controlling the duration and amplitude of responses evoked by these kinases. PHLPP1 is expressed in the mammalian central clock, the suprachiasmatic nucleus, where it oscillates in a circadian fashion. To explore the role of PHLPP1 in vivo, we have generated mice with a targeted deletion of the PHLPP1 gene. Here we show that PHLPP1 -null mice, although displaying normal circadian rhythmicity, have a drastically impaired capacity to stabilize the circadian period after light-induced resetting, producing a large phase shift after light resetting. Our findings reveal that PHLPP1 exerts a previously unappreciated role in circadian control, governing the consolidation of circadian periodicity after resetting.